Taklim Virtual Muslimah pada Masa Pandemi Covid-19 di Wilayah Provinsi Bangka Belitung - Hijrayanti Sari; M. Amirullah; Aswar Aswar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
The Covid-19 pandemic presents its own challenges for the implementation of education, research, and community service. Various adaptations are made so that academic activities can continue to run well, not least the implementation of KKN STIBA Makassar in Bangka Belitung Region. Bangka Belitung Island Province is a province in Indonesia consisting of two main islands namely Bangka Island and Belitung Island as well as hundreds of small islands. The purpose of the implementation of virtual community service is intended so that the condition of pandemic covid-19 is not the reason for the unfulperforming of various muslimah education and coaching activities by students of KKN STIBA Makassar in Bangka Belitung region. The various virtual activities carried out for Muslims are: 1) Virtual weekly Taklim Muslimah; 2) Construction of DIROSA; 3) Tahsin and Tahfiz Online; 4) Virtual Arabic Teaching; 5) Learn Islam Intensively Online; and 6) Pre-Ramadan Webinar. Although in the implementation there are obstacles, such as the condition of the network both participants and committees are less supportive, but the obstacles do not reduce the spirit of da'wah KKN IV STIBA Makassar students in Bangka Belitung Region, to be able to produce twenty active mentors who follow various virtual coaching programs during the kkn period is implemented.